The Advisory Roles of Political Scientists in Europe : Comparing Engagements in Policy Advisory Systems - Brans, Marleen; Timmermans, Arco; Brans, Marleen; Timmermans, Arco (Cham Springer Nature, 2022)
This open access book centres on the advisory roles of political scientists in Europe. Based on a cross-national survey, the book offers a comparative analysis of the viewpoints and activities of university-based political scientists on external engagement. Political scientists in Europe appear more extrovert as academics than sometimes thought. In their professional functioning they engage in delivering knowledge and advice to all kinds of stakeholders in the policy process. This volume contains twelve in-depth country studies where different trends are visible, from political regime change to pressure for impact of academic work. The findings from this comparative analysis may inform our orientation on interaction between academics and their social and political environment, and what this means for education and training in university programs in political science.
English
Keywords: Political science & theory; Public administration; Open Access; policy advisors; policymaking; European politics; political scientists; academic engagement